Effects of Proinflammatory Cytokines on Lacrimal Gland Myoepithelial Cells Contraction - Garriz, Angela; Morokuma, Junji; Bowman, Maytal; Pagni, Sarah; Zoukhri, Driss (Frontiers in Ophthalmology, 2022)
In the lacrimal gland, myoepithelial cells (MEC) express muscle contractile proteins such as alpha smooth muscle actin (SMA) and calponin and therefore can contract to help expel lacrimal fluid. In a previous study, we demonstrated that lacrimal gland MEC express the oxytocin receptor (OXTR) and they contract under oxytocin (OXT) stimulation. Using NOD and MRL/lpr mice (animal models of Sjogren’s syndrome), we reported a decrease in SMA and calponin protein levels plus a decline in acini contraction after stimulation with OXT. It is known that proinflammatory cytokines, such as interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α) or interferon gamma (IFN-γ), can affect OXTR expression and signaling capacity and inhibit MEC contraction. The aim of the current study was to investigate if proinflammatory cytokines are implicated in the loss of MEC contractile ability. Thus, lacrimal gland MEC from a SMA-GFP transgenic mouse were treated with IL-1β (10 ng/ml) for a total of 7 days. At days 0, 2, 4 and 7, GFP intensity, cell size/area, contractile proteins amounts and MEC contraction were assessed. At day 0, control and treated cells showed no differences in GFP intensity and cell size. GFP intensity started to decrease in treated MEC at day 2 (20%; p=0.02), continuing after day 4 (25%; p=0.007) and 7 (30%; p=0.0001). Mean cell area was also reduced at day 2 (34%; p=0.0005), and after 4 (51%; p<0.0001) and 7 days (30%; p=0.0015). The contraction assay at day 2 showed a 70% decrease of contraction in treated MEC (p<0.0001), 73% (p<0.0001) at day 4 and 82% (p=0.0015) at day 7 when compared to control. Levels of contractile proteins were measured on day 7 showing a decrease in SMA and calponin amount in treated MEC compared with the control group (around 30%; p=0.0016 and p=0.0206; respectively). Similar results were observed when TNF-α and IFN-γ were added along with IL-1β. Taken together the present data and those from our previous studies with Sjogren’s syndrome mouse models, they strongly suggest that proinflammatory cytokines affect lacrimal gland MEC contractile ability that may account for the reduced tear secretion associated with Sjogren’s syndrome dry eye disease.